For a Logic of the Event: Language and Philosophy in Process and Reality (Nóema, 2020)
Language represents both one of the most characteristic features of Process and reality and one of the greatest obstacles for the reader. To understand in depth the philosophical reasons why Whitehead adopts such an obscure and complex vocabulary and syntax, the present paper first analyzes Whitehead’s view of ordinary and philosophical language, and then examines the language of Process and Reality in light of such considerations.
Keywords: language; event; common sense; substance; subject; imagination